NUMERICAL MODELING OF INHOMOGENEOUS FLUID SEEPAGE PROCESSES IN FRACTURED POROUS MEDIA (Academia Science Repository, 2023)
The article presents a numerical modeling approach to simulate inhomogeneous fluid seepage processes in fractured porous media. The authors introduce a novel numerical model that combines the finite volume method and the discrete fracture network method to represent the complex fracture networks in porous media. The model is applied to study the inhomogeneous fluid seepage processes in a fractured rock mass and is validated against experimental data. The results show that the proposed model is able to capture the non-Darcian flow behavior and inhomogeneous seepage processes in fractured porous media. The model provides insights into the effects of fracture networks on fluid flow and transport in porous media and can be used to optimize hydrogeological engineering designs. Relevant to researchers and engineers working in the field of hydrogeological engineering, as it provides a comprehensive numerical modeling approach to simulate inhomogeneous fluid seepage processes in fractured porous media. The proposed model has the potential to improve our understanding of the fluid flow and transport mechanisms in fractured porous media and to support the development of effective and efficient hydrogeological engineering designs.